EFEKTIVITAS ANKLE PUMPING DAN INTERMITEN PNEUMATIC COMPRESSION TERHADAP PENURUNAN RESIKO DEEP VEIN THROMBOSIS: KMB - Pardede, Rumiris; Yuniarlina, Risma; Susilo, Wilherlmus Hary (Jurnal Kesehatan, 2020)
Impaired smooth flow of blood to the heart called Deep Vein Thrombosis is still quite high in patients post orthopedic surgery. This study aims to identify the effect of ankle pumping and intermittent pneumatic compression based on an Autar scale assessment in orthopedic surgical patients of the lower extremities. Quasi-experiment study method of pre-posttest design 144 respondents taken by purposive sampling with control 20, intervention 62 ankle pumping, and intervention 62 intermittent pneumatic compression. The results showed that there was no significant effect of ankle pumping intervention (p = 0.436, ? = 0.05) and intermittent pneumatic compression (p = 0.857, ? = 0.05) on the decrease of deep vein thrombosis but at interval ankle pumping age above 40 years (P = 0,001) and mobilization (p = 0,002) showed significant result and intermittent pneumatic compression intervention obtained significant result at mobilization (p = 0.000) to deep vein thrombosis decrease. Ankle pumping can be used as a self-administered nursing action to prevent Deep Vein Thrombosis in post-surgical orthopedic patients. Keywords: Ankle Pumping, intermitten pneumatic compression, Deep Vein Thrombosis, Orthopedi